Secondary Students’ Engagement on Story Completion of Speaking Classroom - Sandra, Repika; Pahlevi, Muhammad Reza; Abas, Totoh Tauhidin (Journal of Teaching of English, 2021)
This study aimed to determine students' engagement on Story Completion in speaking classrooms. The researcher conducted this research in a secondary school in Karawang, which consisted of four students from tenth-grade students. This research used a descriptive case study. The data was collected through interviews and questionnaires. Researchers conducted interviews via WhatsApp call. The questionnaire was distributed through Google Form and used a four-point Likert scale. This study used thematic analysis by Braun and Clark (2006), which includes six steps. It consists of familiarizing the data, generating initial code, searching for themes, reviewing the theme, defining and naming the data, and producing the report. The findings showed that students are positively engaged in emotional, behavioral, and cognitive engagement. In emotional engagement, most of the students gave a positive reaction. The students are enjoyable during the learning. Students showed their willingness to ask questions and do tasks in behavioral engagement. Students showed a high effort to learn in speaking class in cognitive engagement. However, there are obstacles in learning regarding the lack of vocabulary, so that some students find it difficult.